1999
DOI: 10.1023/a:1006257230779
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In a recent paper (Wenderoth et al., J Biol Chem 272: 26985-26990, 1997) we reported that the positions of the two redox regulatory cysteines identified in a plastidic G6PD isoform from potato (Solanum tuberosum L.) differ substantially from those conserved in cyanobacterial G6PDH sequences. To investigate the origin of redox regulation in G6PDH enzymes from photoautotrophic organisms, we isolated and characterized several G6PD cDNA sequences from higher plants and from a green and a red alga. Alignments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In addition, two different types of plastidic G6PDH, P1 and P2, which evolved from a common ancestral gene, were discovered by researchers based on the alignment of mature proteins and signal peptides. The difference in signal peptides between P1 and P2 exists in the cleavage site, which is designated as (I/V/L)X(S/T/K)↓(S) for P1 and (I/V)X(S/T/A)↓(S/T/P/Q) for P2 7 . Furthermore, Wendt et al observed that the P1 and P2 isoforms showed different gene expression patterns in Solanum tuberosum L .…”
mentioning
confidence: 99%
“…In addition, two different types of plastidic G6PDH, P1 and P2, which evolved from a common ancestral gene, were discovered by researchers based on the alignment of mature proteins and signal peptides. The difference in signal peptides between P1 and P2 exists in the cleavage site, which is designated as (I/V/L)X(S/T/K)↓(S) for P1 and (I/V)X(S/T/A)↓(S/T/P/Q) for P2 7 . Furthermore, Wendt et al observed that the P1 and P2 isoforms showed different gene expression patterns in Solanum tuberosum L .…”
mentioning
confidence: 99%
“…The inactivation of G6PD is mediated by thioredoxin (5,7,8,25) and occurs via covalent redox modification of specific regulatory cysteine residues (19). The location of the conserved cysteine residues differs between the cyanobacterial and chloroplast enzymes (19,26), and plants appear to lack any protein with similarity to cyanobacterial OpcA (BLAST search) (12), therefore, regulation of the two enzymes may be quite different. Because the oxidized and reduced forms of G6PD have been shown to differ in their affinities for G6P (19,23,27), we initially considered the possibility that strain UCD 351 G6PD and His-G6PD were in a reduced and inactive form and that the shift in apparent K m we observed was due to oxidative reactivation of the enzyme upon the addition of OpcA.…”
mentioning
confidence: 99%
“…Because the activation of His-G6PD by His-OpcA occurred very rapidly, we could not distinguish between these two possibilities by catalytic assays. Like other cyanobacterial G6PDs, N. punctiforme G6PD contains cysteine residues in conserved positions that may be involved in redox modulation of enzyme activity (26). The N. punctiforme OpcA sequence also contains cysteine residues; of the nine present, those at positions 183, 195, 396, 401, and 407 are conserved in five other cyanobacterial sequences with homology to OpcA and therefore appear to be the most likely targets for thioredoxin-mediated redox modulation of OpcA activity, if it does occur.…”
mentioning
confidence: 99%
“…G6PDHs are tetrameric proteins formed by monomers of ∼50–60 kDa, which are present in all photosynthetic and non-photosynthetic organisms except the Archaea (Wendt et al , 1999). …”
Section: Resultsmentioning
confidence: 99%